2016
DOI: 10.5455/msm.2016.28.288-291
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' Satisfaction with Treatment Opportunities for their Children with Autism Spectrum Disorder in Bosnia and Herzegovina

Abstract: Aim:The goal of this study was to examine the general satisfaction of mothers of children with autism spectrum disorder (ASD) with treatment opportunities for their children in Bosnia and Herzegovina. An additional goal was to assess the level of mothers’ satisfaction with their own involvement in the creation and implementation of Individual Education Plans.Methods:The sample consisted of 98 mothers of children with ASD. Mothers answered to questions related to their perceived satisfaction with treatment opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Existing research on attitudes on BIH teachers was directed towards other disability groups, mainly students with intellectual disability (Memisevic and Hodzic 2011) but not specifically on children with ASD. Unfortunately, there are no population-based studies on the prevalence of ASD in BIH but there is an evident increase in the number of children with ASD attending general education schools in BIH (Mujkanovic et al 2016). Despite this increase of children with ASD attending regular schools, there are no studies that examined teachers attitudes towards their inclusion in regular schools.…”
Section: This Studymentioning
confidence: 99%
“…Existing research on attitudes on BIH teachers was directed towards other disability groups, mainly students with intellectual disability (Memisevic and Hodzic 2011) but not specifically on children with ASD. Unfortunately, there are no population-based studies on the prevalence of ASD in BIH but there is an evident increase in the number of children with ASD attending general education schools in BIH (Mujkanovic et al 2016). Despite this increase of children with ASD attending regular schools, there are no studies that examined teachers attitudes towards their inclusion in regular schools.…”
Section: This Studymentioning
confidence: 99%
“…Thus, the seminars and workshops held by the school where ASD pupil studies helps parents a lot. The absence of community help will increase stress rates in parent of ASD kids, which is the best indicator of anxiety and depression (Mujkanovic et al, 2017). It is a known reality that social assistance could perform a preventative part in decreasing the effect of stress and removing it.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first such study that aimed to identify what teachers believe are the greatest obstacles to inclusion. Previous studies conducted in Bosnia and Herzegovina dealt mainly with the attitudes towards inclusion of students with special educational needs , Dizdarevic, Mujezinovic, & Memisevic, 2017, and a few studies examined the quality of educational support for students with disabilities (Mujkanovic et al, 2016;Mujkanovic et al 2017). Teachers in this study identified what they believe are the greatest obstacles to inclusive education.…”
Section: Discussionmentioning
confidence: 99%